Not-So-Easy Cases. (23rd November 2018) - Crowe, Jonathan
Abstract: The distinction between easy and hard cases is well known from the work of Ronald Dworkin. Dworkin focuses primarily on the challenges posed by hard cases. Easy cases, by contrast, remain relatively under-theorized. This article begins by exploring how judges decide easy cases by relying on holistic intuitive judgments. I then build on this analysis by introducing a third category of cases, which I call not-so-easy cases . I argue that easy, not-so-easy and hard cases are distinguished by the extent to which the judge's intuitive judgments about the factual and legal context for the case yield a clear and determinate outcome. Easy cases are fully resolved at an intuitive level and merely require judges to articulate their decisions; not-so-easy cases are tentatively resolved at an intuitive level but require judges to explain their decisions; and hard cases are unresolved at an intuitive level and require judges to justify their decisions. I offer an account of the decision procedures involved in each type of case. I further contend that most cases heard by appellate courts are not-so-easy cases. The primary task of such courts is therefore best understood as one of explanation (rather than justification ). This finding holds important implications for the nature and legitimacy of the judicial role.